Development of Literation Learning Devices Science Based on Local Wisdom - Nurdin, Syahidan; Ainanur, Nurul; Jannah, Misbahul (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
Lack of learning resources is a problem found at SDN Panton New Area of South Aceh. This makes Literature a curriculum, especially literacy science based on local wisdom in the learning process is important to develop. This research aims to design device learning scientific literacy based on local wisdom and testing feasibility a scientific literacy learning tool based on local wisdom in South Aceh. This research method is research and development that refers on 4D models that is Define (Definition), Design (Design), Develop (Development), Disseminate (Spread). Research result show that the feasibility of science-based literacy learning devices South Aceh's local wisdom was assessed by the media validator obtaining 87.5% in the